More people, more food, worse water? a global review of water pollution from agriculture - Mateo-Sagasta, Javier; Marjani Zadeh, S.; Turral, Hugh (Food and Agriculture Organization of the United Nations, 2018)
Current patterns of agricultural expansion and intensification are bringing unprecedented environmental externalities, including impacts on water quality. While water pollution is slowly starting to receive the attention it deserves, the contribution of agriculture to this problem has not yet received sufficient consideration.